Dynamic human shape description and characterisation. (1st January 2012) - Cheng, Zhiqing; Mosher, Stephen; Smith, Jeanne; Cheng, Huaining; Webb, Timothy; Robinette, Kathleen
Dynamic human shape description and characterisation was investigated in this paper. The dynamic shapes of four subjects in five activities (digging, jogging, limping, throwing, and walking) were created via 3D motion replication. The Paquet shape descriptor (PSD) was used to describe subject shapes in each frame. The unique features of dynamic human shapes were revealed from the observations of the 3D plots of PSDs. The principal component analysis was performed on the calculated PSDs and principal components (PCs) were used to characterise PSDs. The PSD calculation was then reasonably approximated by its significant projections in the eigenspace formed by PCs and represented by the corresponding projection coefficients. As such, the dynamic human shapes for each activity were described by these projection coefficients. To demonstrate potential applications of shape dynamics, a preliminary study was performed on using projection coefficients for activity classification.